Vodenje samoevalvacije v slovenskih poklicnih in strokovnih šolah kot strategija na poti h kakovosti - Pevec, Marija (Revija za elementarno izobraževanje, 2016)
Managing Self-Evaluation in Slovenian Vocational Education and Training Schools as a Strategy on the Path to Quality. The article discusses the phenomenon of managing the process of self-evaluation as it is realized in the segment of secondary vocational education and training in Slovenia. First, we outline the theoretical starting points for assessing and assuring quality in education as well as the scientific findings on self-evaluation made so far, which form the theoretical basis for the empirical research study presented in the second part of the article. The central aim was to examine school self-evaluation practices and needs for expertise in order to carry out and manage the process of self-evaluation. The key findings of the empirical research study (with 231 participating teachers) demonstrate that there are differences in the dimensions of perceiving the self-evaluation process among the schools. The empirical study confirms the presupposition about the need for greater expert support and encouragement of school authorities to managing school quality and establishing the culture of self-evaluation, which are the foundations of the school system for (more) effective and successful quality assessment, monitoring and assurance.
Keywords: self-evaluation; quality; vocational education and training; teachers; head teachers